Case Study of Students' Minconception in Adding and Subtraction Fractions and Their Solutions - Darmawan, Puguh; Rofiki, Imam; Utami, Anita Dewi; Alaiya, Syekha Vivi; Sani, Mutiara (Universitas Islam Sultan Agung, 2024)
This research aims to analyze the causes of students’ misconceptions in addition and subtraction with unlikedenominators, along with their solutions, based on a fishbone diagram. This study was qualitative research with a collective case study design. The research subjects were students who experienced misconceptions in adding and subtracting fractions with unlike denominators. The result of this research was caused by student misconceptions in addition to the subtraction of fractions, unlike denominators, which are classified based on six aspects in the fishbone diagram: man, machine, method, material, measurement, and environment. This causes errors in calculation operations involving numerators and denominators without equalizing fractions, the absence of visual aids for fractions that are unlike denominators, limited teacher mobility in teaching, and a non-conducive classroom atmosphere. Moreover, the language used in textbooks may not be relevant to students’ cognitive levels, and there may be subjectivity in teachers’ assessments of student answers. Peer tutors who provide incorrect explanations to their friends, the existence of certain friendship groups, and high-category students with low communication abilities. Understanding the causes of these misconceptions can be a reference for teachers to prevent misconceptions in students.